2007
DOI: 10.1128/jvi.00505-07
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Reconstruction of Zoonotic and Early Human Severe Acute Respiratory Syndrome Coronavirus Isolates That Produce Fatal Disease in Aged Mice

Abstract: The severe acute respiratory syndrome (SARS) epidemic was characterized by high mortality rates in the elderly. The molecular mechanisms that govern enhanced susceptibility of elderly populations are not known, and robust animal models are needed that recapitulate the increased pathogenic phenotype noted with increasing age. Using synthetic biology and reverse genetics, we describe the construction of a panel of isogenic SARS coronavirus (SARS-CoV) strains bearing variant spike glycoproteins that are represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(120 citation statements)
references
References 66 publications
(88 reference statements)
10
108
1
Order By: Relevance
“…Perhaps this highlights an important intrinsic difference in the species response to virus infection. In future, a heterologous challenge with different SARS-CoV strains is also an important consideration (Rockx et al, 2007). In conclusion, this report adds to others (ter Meulen et al, 2004) that have suggested that a protective SARS vaccine should be possible; however, protection in ferrets (and humans) may be more difficult than the mouse models suggest.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Perhaps this highlights an important intrinsic difference in the species response to virus infection. In future, a heterologous challenge with different SARS-CoV strains is also an important consideration (Rockx et al, 2007). In conclusion, this report adds to others (ter Meulen et al, 2004) that have suggested that a protective SARS vaccine should be possible; however, protection in ferrets (and humans) may be more difficult than the mouse models suggest.…”
Section: Discussionmentioning
confidence: 64%
“…The presence of defective interfering particles common in CoVs might have attenuated the infection in other published challenge studies. Alternatively, the ferrets used in this study were older, and age has been shown to be an important susceptibility factor in the mouse model (Rockx et al, 2007). No other animal, including cynomolgus macaques, has been reported to experience fever, which is the most common sign in human SARS-CoV infection (above 99 %) (Skowronski et al, 2005;Lawler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the segmented genome of the 1918 strain of influenza was reconstructed, in part, by using synthetic design (39). Human endogenous retroviruses were assembled by PCR-directed assembly of synthetic oligonucleotides into a consensus provirus (40), and recombinant SARS-CoVs bearing synthetic zoonotic Spike sequences were derived by our group (22,32). Last, the cloning of the 580-kb microbial genome of Mycoplasma genitalium was reported, although this work has not yet yielded a replicating organism (41).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified zoonotic SARS-CoV variants that replicated efficiently in Vero cells, but not in HAE cultures (22,32). Therefore, HAE cultures provide a more relevant and stringent measure of the replicative potential of chimeric recombinant zoonotic SARS-CoV viruses in the human host.…”
Section: Bat-srbd Replicates In Human Airway Epithelial (Hae) Cell Cumentioning
confidence: 99%